Current Industry Perspective on Process Analytical Technique Tools and their Recent Development in Pharmaceutical Oral Solid Dosage Formulations - Palem, Chinna Reddy; Vamshi Krishna Lekkala (Journal of Pharmacy, 2026)
Current review offers extensive understanding and implementation of process analytical technology (PAT) tools in manufacturing of pharmaceutical oral solid dosage (OSD) forms to streamline product’s time to reach to market and increase profitability. PAT tools provide OSD formulators with an in-depth process understanding that supports accurate and responsive in-line control across all the unit operation, starting from input of raw materials to the delivery of end products. Data collected by PAT tools can be used for improving process understanding and better process control. Recent developments and application of PAT tools in OSD with current industry perspective is an emerging topic over a past decade attracting both academic and industrial researchers. In this review, we covered application of PAT tools in pharmaceutical OSD unit operations (such as blending, granulation, tableting and coating), PAT concepts, PAT tools for OSD, regulatory view, recent developments and application in pharmaceutical industry. By examining current challenges and recent advancements, this review makes a substantial contribution to the evolving field of pharmaceutical manufacturing, bridging key gaps in the existing literature and offering well-founded insights to guide future research and practical applications in the industry.